Predicting vote choice in the 2020 Irish general election. Issue 4 (2nd October 2021) - Elkink, Johan A.; Farrell, David M.
ABSTRACT: This research note has two functions. It first sets the scene for this special issue using the 2020 Irish National Election Study (INES), which comprises several discrete data sets. The note also reports on findings from one part of the INES – an online poll of voters of polling day, which included a battery of questions related to attitudes and behaviours relevant to national politics. The note provides an empirical analysis of the vote choice in this election. Rather than taking a theory-testing approach, we use a more data-driven strategy and identify the key variables in the data set that are of relevance to an understanding of vote choice. Our findings support the views of other recent commentaries of Irish elections that Irish electoral politics is undergoing major transformation. The new electoral politics that is emerging is personified by a clear left vs. right divide in which strongly held ideological positions separate the voters of the main parties.